2018
DOI: 10.4239/wjd.v9.i7.127
|View full text |Cite
|
Sign up to set email alerts
|

Reversibility of diabetes mellitus: Narrative review of the evidence

Abstract: The global disease burden of diabetes mellitus is high. It is well-established that prediabetes is reversible but it is unclear whether diabetes is reversible once it has been diagnosed. The objective of this narrative review is to review the evidence of reversibility of diabetes mellitus and stimulate interest in prolonged remission as a treatment target. The current evidence for bariatric surgery is stronger than intensive medical management and the evidence is stronger for type 2 diabetes patients compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 39 publications
1
10
0
Order By: Relevance
“…The study presented here found that T2DM “remission” indeed occurs in Medicare patients 65 years and older who did not undergo bariatric surgery. These findings are consistent with previous findings and challenge the widespread notion that T2DM is irreversible in non-bariatric settings (13, 24, 25).…”
Section: Discussionsupporting
confidence: 92%
“…The study presented here found that T2DM “remission” indeed occurs in Medicare patients 65 years and older who did not undergo bariatric surgery. These findings are consistent with previous findings and challenge the widespread notion that T2DM is irreversible in non-bariatric settings (13, 24, 25).…”
Section: Discussionsupporting
confidence: 92%
“…Hence, Abdelhafiz et al proposed that frailty among older people with type 2 diabetes might lead to the remission of type 2 diabetes with the suggested mechanisms being weight loss accompanied by reduced amounts of visceral fat and thereby improved insulin sensitivity 32 . Such a mechanism bears resemblance to that described for patients having bariatric surgery and/or substantial weight loss and afterwards experience remission of their type 2 diabetes 34,35 . www.nature.com/scientificreports www.nature.com/scientificreports/ We report that only 17% of included patients had an HbA 1c between 58-75 mmol/mol (7.5-9%), the interval generally recommended for elderly with significant comorbidities and limited life expectancy.…”
Section: Discussionmentioning
confidence: 67%
“…Prior diabetes reversal studies have primarily defined reversal as a binary event that is reached when patients eliminate antidiabetic medications and maintain HbA1c < 5.7% for a year [ 3 , 6 9 , 14 , 15 ]. In the Diabetes Remission Clinical Trial (DiRECT), Lean et al found that 46% of patients in a year-long weight management program achieved diabetes remission (HbA1c < 6.5% at least 2 months after discontinuing all antidiabetic medications) [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…In his review of the evidence for reversibility of diabetes [ 15 ], Ang cited the need for additional research into the subgroups of diabetes patients for whom reversal would be feasible and specifically mentioned the need for research in non-obese patients as well as the SIDD, SIRD, MOD, and MARD subgroups. The current study provides evidence that reversal progression can occur, particularly in the MARD, MOD, and SIRD clusters.…”
Section: Discussionmentioning
confidence: 99%